ECONOMIC DEVELOPMENT OF A SYSTEM TO MONITOR RADON IN INDUSTRIAL FACILITIES AND HOUSING - Baltuano E., O. (2011)
222Rn is formed by the decay of 226Ra , then decays into 218Po and 214Po . Po ions electrostatically produced can be collected using a camera with a polarized high voltage then decays 218Po 214Pb particles emitting at 6.003 keV and thereafter decays 214Po 210Pb emitting particles at 7.687 keV. By measuring the concentration of these alpha particles in the camera can determine the concentration of radon in the air in an indirect way . The prototype has been developed using a measuring chamber 2 L stainless steel of a S3204 -09 PIN diode ( Hamamatsu ) bare body as alpha-particle detector . The camera and diode are polarized with a source of high voltage ( +500 V ) to collect ions and detect Po alpha particles that are then produced in the decay chain . Operations and digital functions are implemented on a PIC18F4550 microcontroller and the device has an internal USB module communication for transferring data to a PC. The configuration of basic parameters is done through a laptop via USB port. Calibration was performed using a system Alfaguard sales team and an area where uranium has been buried for a source of radon , measurements were made at different points with different concentrations of radon. It has been possible to monitor the radon ventilated offices closed and is observed as the variation of radon over several days .